Efeitos do atraso na colheita e do período de armazenamento sobre o rendimento de grãos inteiros de arroz de terras altas - Ribeiro, Gilson José Teixeira (2004)
The present work was develop with a view to evaluating the effect of the delay of harvest on grain moisture and whole grain yield in the processing of 12 rice cultivars as well as the different storage periods upon the recovery of the percentage of whole grains of samples of rice (Oryza sativa L.) harvested at 0, 7, 14, 21 and 28 days after maturation, respectively. Grain samples were also stored determination of the yield of whole grains at 30, 60, 90, 120 and 150 days after harvest of each cultivar. The results showed that the highest yield of whole grains and obtained when harvest is performed with moisture around 20%, the cultivars Caiapó and CNAs 8983 tolerate delay in harvest without further damages to grain yield and the grains for over 90 days maintains of favors the yield of whole grains in processing.